Effect of Inflammatory Signaling on Human Articular Chondrocyte Hypertrophy: Potential Involvement of Tissue Repair Macrophages. (December 2021) - Ferrao Blanco, Mauricio N.; Bastiaansen-Jenniskens, Yvonne M.; Chambers, Mark G.; Pitsillides, Andrew A.; Narcisi, Roberto; van Osch, Gerjo J.V.M.
Objective: In osteoarthritis, chondrocytes tend to acquire a hypertrophic phenotype, which contributes to the modification of the extracellular matrix, resulting in permanent cartilage changes. In mouse chondrocytes, pro-inflammatory macrophages and pro-inflammatory cytokines have been shown to stimulate hypertrophy via the activation of the nuclear factor kappa B (NF-κB) pathway. Whether or not this also occurs in human chondrocytes remains unclear. We therefore aimed to investigate whether hypertrophy-like responses in human cartilage are driven mainly by intrinsic inflammatory signaling or shaped by specific macrophage populations. Design: Human articular chondrocytes were cultured with pro-inflammatory cytokines or medium conditioned by defined macrophage subsets. Furthermore, the effect of inhibition of NF-κB-dependent gene expression was evaluated using the NF-κB inhibitor SC-514. Hypertrophy was assessed by measuring the transcription level of alkaline phosphatase ( ALPL ), type X collagen ( COL10A1 ), Indian hedgehog ( IHH ), and runt-related transcription factor 2 ( RUNX2 ). Results: The expression of hypertrophic genes was not promoted in human chondrocytes by pro-inflammatory cytokines neither pro-inflammatory M(IFNγ + TNFα) macrophages. Inhibition of the NF-κB-dependent gene expression did not affect human articular chondrocyte hypertrophy. However, tissue repair M(IL4) macrophages induced hypertrophy by promoting the expression of COL10A1, RUNX2, and IHH . Conclusion: Intrinsic inflammatory signaling activation is not involved in the hypertrophic shift observed in human articular chondrocytes cultured in vitro . However, tissue repair macrophages may contribute to the onset of this detrimental phenotype in human osteoarthritic cartilage, given the effect observed in our experimental models.